The Relationship Between Supervision, Work Placement, and Organizational Culture with Employee Performance at the Kualuh Hulu Sub-district Office - Soemarjono, Soemarjono; Ikhsan, Ikhsan; Rianto, Dedi; Antoni H, Jeplin; Saskia, Ferina Raisa; Riana, Zeni (Journal of Finance and Business Digital, 2024)
One of the important factors that affect employee performance is supervision. This study aims to analyze the influence of supervision, work placement, and organizational culture on employee performance at the Kualuh Hulu Sub-district Office. The method used is a quantitative approach with data collection through questionnaires distributed to 30 employees. The results of multiple regression analysis show that these three variables have a significant influence on employee performance, with supervision making the greatest contribution. These findings demonstrate the importance of effective supervision, appropriate work placement, and a positive organizational culture in improving employee performance. This study provides recommendations for management to focus on strengthening these three aspects to achieve optimal performance in public services.